Decentralized mobility hubs in urban residential neighborhoods improve the contribution of carsharing to sustainable mobility: findings from a quasi-experimental study - Felix Czarnetzki; Florian Siek (Transportation, 2022)
Carsharing contributes to sustainable urban mobility by reducing private car ownership and use. Thus, policy-makers and planners need to know how cities can foster carsharing and the related benefits. Decentralized mobility hubs are an emerging approach to supporting carsharing. These hubs provide designated carsharing parking spots in the public street spaces of urban residential neighborhoods. The objective is to embed carsharing services into the immediate residential environments of urban households. Thus, the hubs are intended to make carsharing more accessible, reliable, and convenient. However, there is a lack of empirical insights into the impact of decentralized mobility hubs on carsharing. This research uses survey data on carsharing users in the inner city of Hamburg, Germany, to appreciate the actual effects of such hubs on car ownership, transport mode usage, and the perception of carsharing. Decentralized mobility hubs have existed in several high-density residential neighborhoods in Hamburg since 2017. Our findings suggest that the use of these hubs leads to a substantially more positive perception of carsharing and, as a consequence, to a greater willingness of carsharing users to forgo car ownership. Ultimately, by supporting the reduction of private car ownership, the hubs promote not only carsharing, but also the use of other sustainable modes of transportation.
Keywords: 380; Car ownership; Car use; On-street parking; Street space allocation; Multimodality; Urban mobility